Pengaruh Kualitas Produk, Kualitas Pelayanan, Terhadap Kepuasan Pelanggan - Dapot Diarto; Chaerudin Chaerudin (Jurnal Ilmiah Wahana Pendidikan, 2022)
The tight competition in restaurants makes business actors continue to compete in providing satisfaction for their customers. Customer satisfaction is one of the necessary things that need to be maintained to survive in the face of intense competition. Restaurant business actors continue to innovate in every product and quality of service they offer. This study aims to determine the relationship and influence of product qualities and service quality variables on customer satisfaction at the Zonatri Seafood Restaurant. This study uses a quantitative approach method. In this study, 125 respondents using the purposive sampling technique. The data obtained from researcher is primary data or data directly obtained from sources through questionnaires distributed using google forms with measurement techniques using Likert scale measurements. Researchers used multiple linear regression analysis techniques to analyze the data. Based on the results of these studies indicate that the variables of product quality and service quality have a positive and significant influence on customer satisfaction. This study provides theoretical implications as reference material for future research, especially regarding the effect of product quality and service quality on customer satisfaction.